Study of Mn implanted ZnS thin films - "Fakhouri, B" (Kent University,Canterbury, England, 1981)
Zns films in the thickness range of 500A to 1um have been deposited by electron beam deposition, on to mirror polished semiconductor grade Si substrates and on to tin oxide coated pyrex glass at 150/sup 0/C. The film's thickness was measured in situ by a quartz crystal monitor and subsequently by ellipsometry and interferometry. Its refractive index and dielectric constant were found. The current conduction mechanism in un-implanted ZnS films was found to be space charge limited. The I/V characteristics exhibited three distinct regions, ohmic, shallow distributed and a trap-free square law region. The films were annealed in vacuum, argon and nitrogen at 250/sup 0/C for one hour. This had no effect on effective density and effective trap depth but did not reduce the free carrier density on vacuum annealing. Mn ions were then implanted. The overall effect of Mn implantation was the increase of the bulk sensitivity by about three orders of magnitude and the reduction of the mobility by two orders of magnitude. The difference in I/V characteristics was the introduction of a shallow discrete trap level preceeding the shallow distributed trap region of the un-implanted films. It is proposed that this can be represented by effective trap parameters determined from experimental data. (U.K.).
Keywords: "36 MATERIALS SCIENCE"; "ZINC SULFIDES"; "ION IMPLANTATION"; "ANNEALING"; "CARRIER DENSITY"; "CARRIER MOBILITY"; "ELECTRIC CONDUCTIVITY"; "ELECTRODEPOSITION"; "FILMS"; "MANGANESE IONS"; "PERMITTIVITY"; "REFRACTIVITY"; "SILICON"; "SPACE CHARGE"; "SUBSTRATES"; "TEMPERATURE DEPENDENCE"; "THICKNESS"; "TRAPS"; "CHALCOGENIDES"; "CHARGED PARTICLES"; "DEPOSITION"; "DIMENSIONS"; "ELECTRICAL PROPERTIES"; "ELECTROLYSIS"; "ELEMENTS"; "HEAT TREATMENTS"; "INORGANIC PHOSPHORS"; "IONS"; "LYSIS"; "MOBILITY"; "OPTICAL PROPERTIES"; "PHOSPHORS"; "PHYSICAL PROPERTIES"; "SEMIMETALS"; "SULFIDES"; "SULFUR COMPOUNDS"; "SURFACE COATING"; "ZINC COMPOUNDS"; "360605* - Materials- Radiation Effects"